From bulk crystals to atomically thin layers of group VI-transition metal dichalcogenides vapour phase synthesis. (June 2016) - Reale, Francesco; Sharda, Kanudha; Mattevi, Cecilia
Highlights: State-of-the-art of vapour phase synthesis of atomically thin and bulk crystals of TMDs. Physicochemical characteristics of Mo and W halides, organometallic compounds and oxides for CVD synthesis of TMDs. Comprehensive phase diagram of Mo, W, and Ti versus different chalcogens: S, Se, Te. Abstract: Traditional synthesis methods of bulk semiconductors developed during the1970s and 1980s have recently undergone a resurgence of research interest. Physical vapour deposition (PVD), chemical vapour deposition (CVD) and metal organic chemical vapour deposition (MOCVD) have been extensively rediscovered to achieve three-atom thick metal dichalcogenides. Often defined as "graphene-analogous materials" atomically thin sulfides and selenides of group VI of transition metals have revealed a plethora of unforeseen optical, electrical and mechanical properties which make them unique candidates for future nanotechnologies, ranging from quantum electronics to large area consumer electronics. In the last few years tremendous progress has been achieved in the synthesis of high quality atomic crystals, often inspired by the consolidated synthesis methodologies of their bulk counterparts. Most interestingly, several of these methods are still used and also implemented to synthesize new compounds, expanding the range of accessible 2D materials. We review this progress and we highlight key difference in the coordination chemistry of different transition metals which are responsible for the different synthesis products.